2023
DOI: 10.1039/d2qo01529c
|View full text |Cite
|
Sign up to set email alerts
|

A substrate-controlled Ru(ii)-catalyzed C–H activation/[5 + 2] annulation cascade and unusual acyl migration to synthesize diverse indoline scaffolds

Abstract: A substrate-controlled Ru(II)-catalyzed C-H activation/[5+2] annulation cascade and unusual acyl migration to synthesize diversified indoline scaffolds were reported. The most pronounced advantage is that this strategy can offer a highly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In the past decades, transition-metal (TM)-catalyzed and directing group (DG)-assisted inert C–H bond activation (CHA) reactions have been developed as an effective and atom-economic strategy for the construction of C–C and C–X bonds from readily accessible substrates . Based on this strategy, some elegant protocols for the C7–H functionalization of indolines with different coupling partners (CPs) were established . For example, Zhou et al disclosed a Rh­(III)-catalyzed redox-neutral C7-selective CHA/annulation of indolines with alkynes, alkenes, or enynes to furnish 7- or 6-membered 1,7-fused indolines by utilizing N -carbamoyl as an oxidizing DG (Scheme a–d). Wang et al reported a CHA reaction of 3-(indolin-1-yl)-3-oxopropanenitriles with diazo compounds followed by intramolecular cyclization to give seven-membered ring scaffolds (Scheme e) .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, transition-metal (TM)-catalyzed and directing group (DG)-assisted inert C–H bond activation (CHA) reactions have been developed as an effective and atom-economic strategy for the construction of C–C and C–X bonds from readily accessible substrates . Based on this strategy, some elegant protocols for the C7–H functionalization of indolines with different coupling partners (CPs) were established . For example, Zhou et al disclosed a Rh­(III)-catalyzed redox-neutral C7-selective CHA/annulation of indolines with alkynes, alkenes, or enynes to furnish 7- or 6-membered 1,7-fused indolines by utilizing N -carbamoyl as an oxidizing DG (Scheme a–d). Wang et al reported a CHA reaction of 3-(indolin-1-yl)-3-oxopropanenitriles with diazo compounds followed by intramolecular cyclization to give seven-membered ring scaffolds (Scheme e) .…”
Section: Introductionmentioning
confidence: 99%
“…Diazo compounds have been widely used in Rh-catalyzed C–H activations because of their excellent reactivity and high efficiency as reactive synthons. As part of our efforts to study Rh­(III)-catalyzed C–H functionalization strategies for the construction of diversified heterocycle scaffolds, we have been dedicated to using simple substrates to construct diverse polycyclic heterocycle scaffolds. In our latest studies, we surprisingly found that introduction of a dimethyl group into position 3 of 2-pheny-3 H -indole as the C–H activation substrates could construct highly fused indole heteropolycyclic scaffolds with diazo compounds via Rh­(III)-catalyzed successive C–H activation and cyclization cascades under mild reaction conditions with a broad range of substrates in moderate to good yields (Scheme d).…”
mentioning
confidence: 99%
“…2,3 In contrast, the progress of such annulation reactions engaging carbene species that require the involvement of high-valent ruthenium( iv ) intermediates is very limited. 4 This is especially true when a weakly coordinating directing group is considered. An early example was disclosed by the Ackermann group wherein aromatic acids were coupled with sulfoxonium ylides, leading to the formation of functionalized isocoumarins in high yields (Scheme 1a).…”
mentioning
confidence: 99%